The spread of Islam in India and Southeast Asia - Islam, Arshad (Silverfish Books, 2017)
The ancient maritime trading links enabled by the seasonal monsoons between East Africa and China, via the Arabian, Indian and Southeast Asian ports, have played an important but overlooked role in the history of human civilization. The coastal regions of the Indian Ocean represent a cosmopolitan blend of social and cultural diversity enriched mainly by four different civilizations: the Perso-Arabic, the Indian, the Malayan, and the Chinese. Along with goods and technical and scientific knowledge, these trading routes functioned as a conduit for ideas and philosophies, including the religion of Islam. By the end of the seventh century the Arabs had settled in parts of Sri Lanka, and this was the beginning of Muslim penetration in South and Southeast Asia. The fragmentary evidence available reveals the existence of Muslim colonies in different parts of the Malay Archipelago before the mass conversion to Islam took place in the thirteenth century. A comparative study of South Asia and Southeast Asia is therefore essential to understand the eastern dissemination of Islam.